Shaping Minds: The Role of Mass Media in Constructing Public Policy Opinion and Decision Making - Bagale, Sarmila (DMC Journal, 2025)
This study investigates how the media influence government public opinion and policy-making, drawing on behaviour and rational choice theory. In modern democracies, public opinion plays a critical role in shaping government policies, governmental decisions, and social movements. It both reflects societal sentiments and is influenced by formal and informal institutions, with the media—ranging from newspapers, radio, and television to digital platforms—serving as a central actor. Often described as the fourth pillar of democracy, the media mobilizes citizens, fosters dialogue, exposes injustices, and monitors power, shaping narratives that influence collective perceptions. However, misuse of media can undermine democratic processes. Using a focus group discussion approach with randomly selected participants from Bharatpur Metropolitan City communities, this paper examines the mechanisms through which media affect political understanding and decision-making. Findings indicate that mass media significantly shape public opinion, set societal agendas, and influence perceptions of government initiatives. The study further highlights the growing importance of social media platforms in mobilizing citizens and disseminating policy information. The study concludes that media remain indispensable in informing the public and guiding perceptions of governance and development programs. It recommends that government communication strategies incorporate local dialects to enhance comprehension and engagement across both urban and rural populations.